Po drugiej stronie lustra. Nieziemski ołtarz w „Obleżeniu Jasnej Gory Częstochowskiej” - Kowalski, Jacek (TECHNE. Seria Nowa, 2018)
The poem Siege of Jasna Góra, probably written in the years 1669–1673, is one of the most outstanding Polish baroque epics. The author modeled on Torquat Tass’s Jerusalem Delivered, but he described contemporary events – the defense of the Pauline monastery at Jasna Góra (the national sanctuary of Our Lady of Czestochowa) before the invasion of the Protestant Swedes (1655). In Canto XI there is a description of a journey to the afterlife – a typical element of many ancient and modern epics. The main character, Lioba, is guided around the heaven by Saint Paul the Hermit, founder of the Pauline order. She is watching in the sky an unusual, glittering, huge church with one alabaster body. The church is decorated with mosaics made of precious stones, representing the Seven Sorrows of Mary. The place of the main altar occupies a huge mirror; it is like a window and a picture. The light emanating from Empireum evokes in this mirror most images of pious and heroic deeds performed by Catholics on four continents. Sinful Poles gather in the church. Archangel Michael strikes with the sword at the pawiment, which collapses, and the sinners fall into the abyss. The author of the description uses the patterns of ekphrasis contained, among others poems written earlier by Samuel of Skrzypna Twardowski (ca 1595/1600 – 1661). The original idea is a description of the altar, which is also a mirror and a window open to holy history. Probably it is a reference to the known species speculum, describing patterns of virtues and behaviors. The article argues – contrary to earlier studies – that the church described is not a picture of the Heavenly Jerusalem, but a parabole of church fighting, pilgrim on the earth. The author of the poem refers to the concept of Ecclesia militans, as the Mystical Body of Christ; at the same time, sinners and saints are included in this church. The literary vision refers to the tradition of ekphrasis, but at the same time agrees with the then ideals of baroque architecture: the unity, magnitudo and magnificenza.